2017
DOI: 10.1097/mpg.0000000000001504
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Practices and Growth in Premature Infants After Surgical Necrotizing Enterocolitis

Abstract: Postoperative protein doses in infants with surgical NEC appear related to increases in HC. The influence of postoperative nutritional support on risk of adverse outcomes deserves further attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The complexity of balancing such trade-offs is highly relevant for infants who are VLBW in the immediate postnatal period and infants made NPO for feeding intolerance or evaluation and management of NEC/SIP. 20 The findings of this study suggest the following recommendations to maximize energy and protein intake in VLBW infants: (1) deliver PN and intravenous lipids through phase 3 (≤66.7% enteral) to maximize energy intake; (2) consider PN through phase 4 (<100% enteral) to maximize protein intake;…”
Section: Discussionmentioning
confidence: 86%
“…The complexity of balancing such trade-offs is highly relevant for infants who are VLBW in the immediate postnatal period and infants made NPO for feeding intolerance or evaluation and management of NEC/SIP. 20 The findings of this study suggest the following recommendations to maximize energy and protein intake in VLBW infants: (1) deliver PN and intravenous lipids through phase 3 (≤66.7% enteral) to maximize energy intake; (2) consider PN through phase 4 (<100% enteral) to maximize protein intake;…”
Section: Discussionmentioning
confidence: 86%
“…Optimizing growth in these infants can improve neurodevelopmental outcomes [2]. It is known that higher parenteral protein provision following surgery for NEC leads to improved head circumference growth [3]. Understanding which of these factors are modifiable will assist care providers in focusing resources.…”
Section: Introductionmentioning
confidence: 99%
“…A pilot study showed that the whole protein turn-over in neonates with proven NEC is comparable to the value in stable neonates, and that neonates with NEC may divert the products of protein synthesis from growth to tissue repair [ 28 ]. A prospective study compared a high dose of protein (median daily dose 3.87 g/kg) versus a low dose of protein (median daily dose 2.80 g/kg) during the first week after surgery for NEC, showing no difference in body growth with the exception for head growth (increased in the first group), however, of significant concern, non-survivors received less protein than survivors [ 10 ]. Regarding the composition of aminoacidic solutions, few data are available: Glutamine is the most abundant free amino acid in the body and it is the preferred respiratory fuel for rapidly proliferating cells.…”
Section: After Surgerymentioning
confidence: 99%
“…Bowel rest is the main therapeutic strategy in medical NEC, therefore PN is required after NEC onset regardless of the severity. PN is necessary during the acute phase as the only nutrition support and must be adapted to the rapid metabolic changes after NEC onset [ 10 ]. At the same time, it is essential during the recovery phase when enteral nutrition does not satisfy total nutrients’ requirement and especially if extensive bowel resection causes IF [ 11 ].…”
Section: Introductionmentioning
confidence: 99%